The Development of Learning Activities by Open Approach on the Topic Political Regime to Enhance Problem Solving Ability of Mathayom Suksa 4 Students - Ussapan, Chaidilok; Laosuwan, Dr.Tatchawat (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
The purposes of this research were to development of Open Approach learning activities on The Topic Political Regime for Mathayom Suksa 4 students. The sample were two classes of Mathayom Suksa 4 at the Nampong secondary school. Which is a Quasi-Experimental research. The Research instruments were (1) 10 Open Approach learning Lesson Plan, (2) the problem solving ability test, (3) the student’s satisfaction questionnaire for organizing Open Approach learning activities. The research results were found that, (1) The efficiency of Open Approach learning activities on The Topic Political regime Mathayom Suksa 6 were 85.62 / 80.15, (2) The percentage average score of problem solving ability of the experimental group after learning was higher than before learning at .05 level of significance, (3) After the experiment, the percentage average score of problem solving ability of the experimental group was higher the control group at .05 level of significance, (4) students’ satisfaction with Open Approach learning on The Topic Political regime for Mathayom Suksa 4 students on overall was at the high level were mean at 4.09.